Synthesis of Ag Doped ZnO Nanowire by Hydrothermal Method and its Characterization - Luitel, Utsab; Sapkota, Kamal Prasad; Shrestha, Santu; Paudel, Dasu Ram; Pradhan, Sharmila (Journal of Nepal Chemical Society, 2024)
This research is mainly focused over synthesizing zinc oxide (ZnO) nanowire (NW) and silver doped zinc oxide nanowires (Ag/ZnO) using two step hydrothermal method which comprises of seed layer deposition and hydrothermal nanowire growth step. Hydrothermally grown nanowires are of great significance. The synthesized nanowires were characterized by UV-Vis Spectroscopy (UV-Vis), X- ray Diffraction Spectroscopy (XRD), Energy Dispersive Spectroscopy (EDS), Field Emission Scanning Electron Microscopy (FE-SEM) and High-Resolution Transmission Electron Spectroscopy (HR-TEM). XRD pattern revealed as-synthesized materials are of crystalline nature having crystallite size of 166.27 nm and 42.32 nm for ZnO nanowire and Ag doped nanowire, respectively. Further confirmation was done by EDS, SEM and TEM. The microscopic images of SEM and TEM evidenced for successful fabrication of nanowires.